Pekanbaru Creative Center Dengan Pendekatan Arsitektur Folding - Oktaviani, Sundari Fitria; Aldy, Pedia; Faisal, Gun (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Pekanbaru Creative Center is a place that has functions for education, sharing, collaboration, commercial, and performances that will become a forum for the creative industry community and the community to support creative industry activities while at the same time maximizing the existing potentials. It will later focus on facilitating the development of the 8 most superior sectors in Riau according to Bekraf (2016), namely culinary; craft; film, animation and video; application and game developer, architecture, DKV, performance art, and fashion. With the development of the creative industry in Pekanbaru it is hoped that it will become one of the solutions to economic problems by creating jobs. Pekanbaru Creative Center will be located in Pekanbaru City. The city of Pekanbaru was chosen based on the distribution of creative economy actors in Riau, 58.62% of which are in Pekanbaru while the rest are scattered in other Riau regions. The existence of the Pekanbaru Creative Center is expected to be a forum for the people of Pekanbaru, starting from students, freelancers, creative industry players , start-up actors and visitors from the general public who have the desire to learn and develop their work into tangible results and have more selling power. In designing the Pekanbaru Creative Center will use the Folding Architecture approach. Folding Architecture is a process of producing a formation in architectural design which is essentially experimenting to produce a form through a process Its application to architectural design uses paper characters and transforms them into a form through the Folding process and the nature of folding architecture. There will be 3 buildings which are divided based on the function of the building, they are the manager and public buildings, training buildings, as well as food court buildings and prayer rooms. The application of the Folding process to buildings will be limited by the concept of buildings, origami. There are three origami that will limit each building..keywords: Pekanbaru, Creative Center, Folding Architecture